Impact of Socio-economic Status on Age at Menarche among Secondary School Students at AL-Dora Region in Baghdad Governorate - wadi, Sahar; Abdul Jabbar, Khalida (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To assess the Impact of Socio-economic status on age at menarche among secondary school students atAL-Dora city in Baghdad, Iraq.Methodology: This is a cross sectional study with multi-stage sampling was carried out during the period from the3th of December2013 to 12th of March 2014. The Sample comprised of 1760 girls, 1510 girls from urban area and250 from rural area was included in the study. In first stage, selection of schools was done, and one class wasselected randomly from each level of Education, The data collection through a special questionnaire which Containthe age of girl by year, class level, birth order, number of household, number of rooms, residency (urban/rural),education level of parents, occupation of parents.Results: The study showed that the mean age at menarche for adolescent secondary school girls in Al-Dorawas12.49±0.99 years, and the mean age at menarche of girls living in the urban area were 12.4±1.0 while 12.9±1.1year for girls living in the rural area, which give a significant association, so the girls from urban area had earliermenarche age than rural area, and earlier age at menarche of those girls who had fewer number of siblings thanthose who had more siblings, Also the study discovered an earlier age at menarche in those girls whose Parents’had a high educational level, occupation of mothers, While there was no association between occupation of fatherand age at menarche.Recommendation: According to the findings of the present study we recommended to further elaborated study isrequired to estimate the age of menarche of Iraqi girls, because menarche age can vary by location, it may not bepossible to generalize these results to other communities in the Iraq government